Pengenalan teknik Pembuatan Kapsul Black Garlic di Desa Sembalun Bumbung - Sopiati Alawiyah; Mia Maharani Dewi; M. Sarjan (Pascasarjana Universitas Mataram, 2020)
Introducing an appropriate technology by University of Mataram student group of KKN ( Kuliah Kerja Nyata) or Community Service program was conducted in Sembalun Bumbung village Sembalun District, East Lombok Regency, West Nusa Tenggara Province. One of the aim of this program is to improve the added values of local existing product suchof as “Black Garlic” that was modified into into Black Garlic Capsules. The program targeted partners of farmer groups, youths, and PKK (Pendidikan Keseahteraan Keluarga) group by providing information on knowledge transfer and fermented garlic skill becomes a food product ( Black Garlic Capsules) as the prospective business opportunity to increase the economy of the local community. The methods used in this program including the steps as follows , Intoducing the research on the development of black garlic, the demonstration and training on product manufacture , packaging and marketing training, assisting and mentoring to partnership and conducting evaluation during training. The result of this program showed a positive response from village officials and its local people as c indicated byan be seen from the enthusiasm of the participant during the training and actively involved in the partnership. In addition, from this program indicated that the rapid knowledge improvement of the partnership on producing Black Garlic, the skill and capability improvement in practicing the processed product by the partnership , as well as it makes them interested to produce black garlic capsules to gain additional income for their family.